(untitled) (Khairulummah, 2022)
Haq Mehr, also known as dowry, is a customary practice in Islamic marriages where the groom gives a mandatory payment or gift to the bride. This abstract explores the concept of Haq Mehr and its significance in Islamic teachings. The discussion covers various aspects related to Haq Mehr, including its definition, types, and recommended practices. It emphasizes the importance of understanding the cultural, social, and legal considerations when determining the Haq Mehr. The work also highlights the obligations and recommendations associated with Haq Mehr. It discusses various sources, such as the Quran, Hadith, Islamic jurisprudence, and local customs, which guide the determination and payment of Haq Mehr. Furthermore, the research work sheds light on the implications of not fulfilling the Haq Mehr obligations and the potential consequences on marital relationships and legal rights. In conclusion, this abstract provides a comprehensive overview of the concept of Haq Mehr and emphasizes its cultural, religious, and legal significance in Islamic marriages. It serves as a valuable resource for individuals seeking a deeper understanding of Haq Mehr and its implications in the context of Islamic teachings.